2012
DOI: 10.3109/0886022x.2012.745727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peripheral and Respiratory Muscle Training on the Functional Capacity of Hemodialysis Patients

Abstract: Patients on hemodialysis (HD) show changes in muscle structure and function reducing their functional capacity. This study was conduted to assess the effects of respiratory muscle training (RMT) and peripheral muscle training (PMT) during dialysis on functional parameters, inflammatory state, and quality of life (QoL) in patients on HD. Randomized controlled trial included 39 patients on HD, and they were divided into three groups: RMT (n = 11), PMT (n = 14), and controls (C, n = 14). Training was performed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 31 publications
7
125
0
8
Order By: Relevance
“…Another study performed inspiratory muscle training for eight weeks in 15 patients and found no increase in inspiratory muscle pressure (MIP) (11) . In contrast, the results of a randomized controlled study showed that 10 weeks of IMT improved inspiratory strength and functional performance, but that pulmonary function did not benefit by this training (12) . Thus there is little conclusive evidence in the literature on IMT in HD patients and we hypothesized that six months of IMTcan improve respiratory variables and aspects related to quality of life of HD patients.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Another study performed inspiratory muscle training for eight weeks in 15 patients and found no increase in inspiratory muscle pressure (MIP) (11) . In contrast, the results of a randomized controlled study showed that 10 weeks of IMT improved inspiratory strength and functional performance, but that pulmonary function did not benefit by this training (12) . Thus there is little conclusive evidence in the literature on IMT in HD patients and we hypothesized that six months of IMTcan improve respiratory variables and aspects related to quality of life of HD patients.…”
Section: Introductionmentioning
confidence: 85%
“…To obtain findings for the effects of resistance training on the respiratory muscles, beyond the Principle of Overload, the specificity (inspirations of high intensity and short duration) was taken into consideration (27) . In the literature, three published studies have evaluated the effects of IMT on patients receiving HD (10)(11)(12) only one study was randomized and controlled (10 weeks of treatment, three sets of 15 inspirations, three times per week and during hemodialysis) and showed a significant increase in respiratory muscle strength and in aspects related to quality of life (12) . The improvement in respiratory strength in this study was probably owing to adaptations by the inspiratory muscles linked to the type of training (moderate load) that promotes hypertrophy (increase in muscle strength), increases the proportion of type I fiber, reduces type II fiber and increases the cross-sectional area in the diaphragm (7,8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients usually cycle for 10-45 min and progressively resistance is applied to the bicycle wheels [72][73][74][75][76][77][78][79][80][81][82]. Also, resistance exercises have been applied in intradialytic exercise training programs without serious complications and induced beneficial effects on patient's muscular strength [83][84][85][86][87][88][89][90] The exercises sessions occurred at the hemodialysis centers during the first two hours of the hemodialysis treatment (table 4). According to Moore et al [41] is more safe exercise training programs to be applied during the first 2 hours because cardiac function is more stable.…”
Section: Effects Of Intradialytic Exercise Programsmentioning
confidence: 99%
“…In a randomised trial of patients undergoing haemodialysis (Pellizzaro et al, 2013), patients who underwent inspiratory muscle training 3 times per week for 10 weeks at an intensity of 50% of maximum inspiratory pressures demonstrated greater gains in inspiratory muscle strength than those who completed only peripheral exercise or no exercise while on dialysis. Greater gains were also seen with the inspiratory muscle training group compared with the control group in distance walked during the 6 minute walk test (65 m versus -0.5 m respectively).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%